Parity of level neuron-specific enolase and a brain blood-groove at hemispheric ischemic stroke - G. M. Karyakina; M. V. Nadezhdina; M. A. Hinko; N. M. Gurariy (Бюллетень сибирской медицины, 2009)
An inspection is conducted 60 patients with hemispheric ischemic stroke in age from 51 to 69 years, part on the degree of expressed of neurological deficit in obedience to the Scandinavian scale (19,0 ± 1,9) – I group (27), (41,1 ± 3,5) is II a group (33). The comparative analysis of neurological deficit is given, level neuron-specific enolase (NSE) in blood, hemodynamic indexes, character of atherosclerotic name-plates, exposed on the basis of ultrasonic duplex research of main arteries of cerebrum in a dynamics. Dependence is exposed between expressed of neurological defect, degree of damage of fabric of brain, characterized by the change of level of NSE and degree of disturbances of hemodynamic. Clear dependence is marked between a neurological defect and decline (p < 0,05) of high systole speed in a poststenotic area. Character of atherosclerotic name-plates reflected pathogenic of ischemic stroke.